2013
DOI: 10.14260/jemds/769
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency as a Risk Factor for First Febrile Seizure

Abstract: Estimation of Iron status in children with first febrile seizure (FFS). Iron status was evaluated by including Hemoglobin, Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH), Serum ferritin. MATERIALS AND METHODS: Study was conducted all children with first febrile seizures and febrile illnesses (FI) in Pediatrics Intensive Care Unit and Pediatrics Wards of Sri Adichunchanagiri Institute of Medical Sciences, B.G. Nagara from January 2010 to June 2011. The blood samples from the 50 children compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…HB, HCT, MCH, mean serum ferritin and serum iron, were significantly low in the febrile convulsion group as compared to control group (Table 2). Similar results found in different studies Ahmed 9 and Majumdhar et al 10 analyzed for Iron deficiency as a risk factor for febrile convulsion, by biochemical and hematological investigations. In Majumdhar R et al 10 study mean Hb, MCV and MCH was 8.92g%, 67.03 fl, 30.66 pg respectively which was significantly low in cases compared to control.…”
Section: Discussionsupporting
confidence: 87%
“…HB, HCT, MCH, mean serum ferritin and serum iron, were significantly low in the febrile convulsion group as compared to control group (Table 2). Similar results found in different studies Ahmed 9 and Majumdhar et al 10 analyzed for Iron deficiency as a risk factor for febrile convulsion, by biochemical and hematological investigations. In Majumdhar R et al 10 study mean Hb, MCV and MCH was 8.92g%, 67.03 fl, 30.66 pg respectively which was significantly low in cases compared to control.…”
Section: Discussionsupporting
confidence: 87%
“…Average mean of MCH in case group was statistically significantly lower than normal (30.96±3.58 gms), while in control group it was within normal (32.68±2.32 gms). It came in agreement with Khanna et al (12) , Jang et al (13) , Tripathy et al (15) , and Majumdhar et al (19) .…”
Section: Discussionsupporting
confidence: 91%
“…This was quite similar to result of studies of Khanna et al (12) and Noorbakhsh (17) . While in Surani et al (14) mean MCV was (8.87 g/dl) and in Majumdhar et al (19) it was (67.03 fl).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…URTI, as in present study is also the most common etiology of fever in other studies too. Study by Majumdhar et al 14 had URTI as the commonest cause with no statistical difference with control group. Sultan et al 18 found respiratory tract infections as the commonest cause (78% in cases).…”
Section: Discussionmentioning
confidence: 88%